2017
DOI: 10.26850/1678-4618eqj.v42.1.2017.p40-50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of redox potential on chalcopyrite dissolution imposed by addition of ferrous ions

Abstract: ABSTRACT:Copper is one of the metals with great economic interest and about 70% of it is found in nature as chalcopyrite mineral (CuFeS 2 ). Due to its slow dissolution kinetics, chalcopyrite dissolution is still a challenge for industries and researchers. Control of redox potential though has been said to be the key for increasing dissolution rate in chalcopyrite leaching systems. The current work investigated the effect of redox potential by ferrous ions addition on chalcopyrite (bio)leaching experiments. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Santos et al also observed an increase from 300-400 mV to 570-600 mV (Ag/AgCl/KCl) in leaching solution Eh during the seven first days of chalcopyrite bioleaching by A. ferrooxidans, under different ferrous ions concentrations [35]. Redox potential of leaching solution is recognized as one of the most important issues on chalcopyrite bioleaching and it is mainly controlled by the [Fe 3+ ]/[Fe 2+ ] ratio dynamics along the process [35]. One of the proposed mechanisms is that Eh must allow the initial reduction of chalcopyrite to chalcocite (Cu 2 S) and its subsequent oxidation and releasing the soluble copper which is achieved under 400-450 mV (Ag/AgCl/KCl) [10].…”
Section: Ph and Eh Monitoringmentioning
confidence: 86%
See 1 more Smart Citation
“…Santos et al also observed an increase from 300-400 mV to 570-600 mV (Ag/AgCl/KCl) in leaching solution Eh during the seven first days of chalcopyrite bioleaching by A. ferrooxidans, under different ferrous ions concentrations [35]. Redox potential of leaching solution is recognized as one of the most important issues on chalcopyrite bioleaching and it is mainly controlled by the [Fe 3+ ]/[Fe 2+ ] ratio dynamics along the process [35]. One of the proposed mechanisms is that Eh must allow the initial reduction of chalcopyrite to chalcocite (Cu 2 S) and its subsequent oxidation and releasing the soluble copper which is achieved under 400-450 mV (Ag/AgCl/KCl) [10].…”
Section: Ph and Eh Monitoringmentioning
confidence: 86%
“…An increase to 600 mV was observed after the 6th day until the 21th day in the reactor 2 amended with the weathered ore probably due to the accumulation of Fe 3+ in the absence of reduced mineral sulfides, reaching a final value of 586 mV at the 50th day ( Figure 7B). Santos et al also observed an increase from 300-400 mV to 570-600 mV (Ag/AgCl/KCl) in leaching solution Eh during the seven first days of chalcopyrite bioleaching by A. ferrooxidans, under different ferrous ions concentrations [35]. Redox potential of leaching solution is recognized as one of the most important issues on chalcopyrite bioleaching and it is mainly controlled by the [Fe 3+ ]/[Fe 2+ ] ratio dynamics along the process [35].…”
Section: Ph and Eh Monitoringmentioning
confidence: 98%
“…The obtained results support the earlier study suggesting that the dissolution of chalcopyrite appears to be an acidic consuming reaction [27] B. Leaching solid residue XRD characterization Figure 3, Tables 3 and 4 show the mineral content of the various solid residues collected according to the red dots as shown on the Cu dissolution curve. The progressive chalcopyrite dissolution was observed; a decrease in its major peak intensity was noticed suggesting an effective mineral dissolution [28]. In addition to that, the Cu dissolution appeared to be accompanied with new mineral phases formation.…”
Section: A Leachate Characterizationmentioning
confidence: 90%
“…Os valores obtidos a partir da metade do experimento, próximos a 580mV, foram semelhantes aos obtidos por Mejía et al (2015) [23], que realizou biolixiviação da calcopirita em frascos agitados por 30 dias, empregando A. ferrooxidans. Santos e colaboradores [24] observaram valores de Eh variando entre 300 a 470mV em condições abióticas de oxidação da calcopirita, enquanto que na presença da bactéria A. ferrooxidans LR, os valores de Eh observados foram próximos a 600mV, semelhante aos observados no presente estudo.…”
Section: Monitoramento Do Ph E Ehunclassified